Tourist Safety Risk Management at Piala Waterfall Banggai Regency, Indonesia: A HIRARC-Based Analysis - Asti Ayuningsih; Novita Restiati Ina Wea (Faculty of Economics and Business, University of Mataram, 2026)
The fast-growing nature-based tourism in Indonesia is not accompanied by academic research. Recent academic research has focused more on destination development and visitor satisfaction, leaving a large gap in research on technical safety assessment and hazard management in natural environments. The current research fills this gap by providing a systematic safety risk analysis at the Piala Waterfall, Banggai Regency. The study was carried out in December 2024 using a qualitative descriptive design. Data were collected through field observation and in-depth interviews with three key informants: destination managers and workers. The novelty of this research lies in the specific application of the Hazard Identification, Risk Assessment and Risk Control (HIRARC) framework, which is typically used in an industrial setting, to the unpredictable and dynamic environment of a waterfall destination. The study found that the most ‘Extreme’ risks stem from natural factors and visitor behaviour, whereas ‘High’ risks are attributed to infrastructure deficiencies such as messy steps. The theoretical contribution is the adaptation of the semi-quantitative safety science models to nature-based tourism to fill the gap between hydrological hazards and administrative management. On the practical aspect, the research offers a blueprint for the local authorities on the implementation of engineering and administrative controls such as consistent safety signage and seasonal closures to improve the sustainability and resilience of the destination.